A Forty Year Assessment of Forecasting the Boat Race - Geert Mesters; Siem Jan Koopman (Tinbergen Institute, 2012)
We study the forecasting of the yearly outcome of the Boat Race between Cambridge and Oxford. We compare the relative performance of different dynamic models for forty years of forecasting. Each model is defined by a binary density conditional on a latent signal that is specified as a dynamic stochastic process with fixed predictors. The out-of-sample predictive ability of the models is compared between each other by using a variety of loss functions and predictive ability tests. We find that the model with its latent signal specified as an autoregressive process cannot be outperformed by the other specifications. This model is able to correctly forecast 30 out of 40 outcomes of the Boat Race.
urn:NBN:nl:ui:31-1871/38766
Keywords: C32; C35; 330; Binary time series; Predictive ability; Non-Gaussian state space model; Prognoseverfahren; Stochastischer Prozess; Zustandsraummodell; Theorie